The effects of western diet on sperm quantity and quality and serum hormonal concentration in cynomologus monkey (Macaca fascicularis) injected with testosterone enanthate (TE) plus depot medroxy progesterone acetate (DMPA+) (Medical Journal of Indonesia, 1997)
[no abstract available]